The Influence of the Self-Help Housing Stimulant Assistance Program (BSPS) on Increasing Community Welfare in Tanjungpinang City - Romadhon, Asif Rizky; Nazaki, Nazaki; Darmawan, Eki (Contemporary Journal of Applied Sciences, 2024)
People with low incomes have limited resources that can only be spent on food, health and education but find it difficult to meet high housing costs which threaten the material well-being and economic security of households (OECD, 2011). 285 BSPS program units have been given to the people of Tanjung Pinang City. This research aims to find out whether the BSPS program affects improving welfare. This research uses a causal associative quantitative approach. The research results prove that the t-test shows that t-count (3.917) > t-table (1.993), so Ha is accepted, thus proving that the BSPS program has effects on improving community welfare in Tanjung Pinang City. Recipients of the BSPS program in Tanjung Pinang City experienced increased welfare after receiving the program. This is supported by previous research which shows that the BSPS program improves community welfare.